Analysis of variables affecting competitiveness of SMEs in the textile industry - Taçoğlu, Caner; Ceylan, Cemil; Kazançoğlu, Yiğit (Journal of Business Economics and Management, 2019)
This paper aims to develop strategy and policy suggestions to increase the competitiveness of SMEs in the textile industry by analyzing the variables that affect competitiveness and contribute to competitiveness literature by adopting a holistic approach to the analysis of competitiveness variables. A hybrid model composed of Delphi and fuzzy DEMATEL (Decision-Making Trial and Evaluation Laboratory) methods were used to gather and analyze the competitiveness variables. This led to the identification of the 15 most important of 73 competitiveness variables relevant to SME competitiveness in the textile industry. These variables were analysed and ranked, and their causal relationships were mapped. The results obtained from the model may function as a reference for SME managers aiming to increase their firm’s competitive power.